2020
DOI: 10.1101/2020.06.22.166041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A whole-cortex probabilistic diffusion tractography connectome

Abstract: AbstractThe WU-Minn Human Connectome Project (HCP) is a publicly-available dataset containing state-of-art structural, functional, and diffusion-MRI for over a thousand healthy subjects. While the planned scope of the HCP included an anatomical connectome, resting-state functional-MRI forms the bulk of the HCP’s current connectomic output. We address this by presenting a full-cortex connectome derived from probabilistic diffusion tractography and organized into the HCP-MMP1.0 a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…Moreover, we observed that features related to important AD-related functional networks (as the default-mode network (Grothe, Teipel et al 2016) and the visual ventral stream (Grill-Spector and Malach 2004, Kravitz, Saleem et al 2013)) are involved with a higher feature importance rank. A table with the full name and corresponding functional network according to Rosen and Halgren (Rosen and Halgren 2020) for the 50 highest ranked features is given in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we observed that features related to important AD-related functional networks (as the default-mode network (Grothe, Teipel et al 2016) and the visual ventral stream (Grill-Spector and Malach 2004, Kravitz, Saleem et al 2013)) are involved with a higher feature importance rank. A table with the full name and corresponding functional network according to Rosen and Halgren (Rosen and Halgren 2020) for the 50 highest ranked features is given in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Parcellation adapted from(Glasser, Coalson et al 2016). Functional networks adapted from(Rosen and Halgren 2020). DS: Dorsal Stream, VS: Ventral Stream, SMA: Supplementary motor area…”
mentioning
confidence: 99%
“…It follows that only approximately 1% of cerebral neurons project to the contralateral hemisphere. This assertion is supported by modern data from the human connectome project showing that cerebral connectivity is completely dominated by ipsilateral connections [30], and that less than 1-2% of hippocampal projections, for example, are contralateral [31]. The fraction of crossing connections from brainstem nuclei in humans has not been reported in detail.…”
Section: The Human Connectome and The Soc Modelmentioning
confidence: 95%
“…The scarce contralateral projections underlie an-other element of the SOC model. Most cortical re-gions and some subcortical structures send most of their commissural projections to their contralateral homologs, so called homotypic connections (illustrated in Fig.3 A) [ 30 ]. If brain-first PD is most com-monly initiated in a single unilateral structure, such as the entorhinal cortex or amygdala, the first structures to be affected in the contralateral hemisphere will also be the amygdala or entorhinal cortex [ 33, 45 ].…”
Section: The Human Connectome and The Soc Modelmentioning
confidence: 99%
“…In order to compare the functional connectivity metrics to the underlying corticocortical white matter connectivity, we reorganized our previously published diffusion-MRI based structural connectome [15] in which connectivity was assessed among the 360 cortical areas of the HCP-MMP1.0 atlas [7]. Of the 100 IC nodes, 46 are composed of at least 40% cortical voxels (Fig.S6A) and as the dMRI connectome was restricted to corticocortical relationships, we limited the scope of our analyses to these nodes.…”
Section: Supplementary Materialsmentioning
confidence: 99%